Low-adhesion magnetic soft composite antibacterial coating as well as preparation method and application thereof

Through the directional saturation magnetization and saturated bloating treatment of low -adhesive magnetic software composite materials, combined with the vortex removal technology driven by cyclical motion magnetic magnetic array, the problem of low resistance to antibacterial coating and toxic substances has been solved. Effect.

CN119371894AActive Publication Date: 2025-01-28SHANGHAI JIAOTONG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411435944.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-28
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing antibacterial coatings have low durability and contain toxic substances in the formulation, which limits its application range.

Method used

Using low -stick magnetic software composite materials, through targeted saturation magnetization and saturated bloating treatment, prepare antibacterial coating with good durability, and drives cyclical dynamic deformation by designing cyclical motion magnetic magnetic arrays to form a vortex removing bacterial adhesion to remove bacterial adhesion Essence

Benefits of technology

The high durability and good sterilization effect of antibacterial coatings are achieved, and it avoids the use of toxic substances and good biocompatibility and magnetic control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371894A_ABST
    Figure CN119371894A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of antibacterial coating manufacturing, and particularly relates to a low-adhesion magnetic soft composite antibacterial coating and a preparation method and application thereof.The low-adhesion magnetic soft composite antibacterial coating is obtained by conducting directional saturation magnetization on a magnetic soft composite after the magnetic soft composite is cured and conducting saturation swelling treatment on the surface of the magnetic soft composite. The magnetic soft composite material comprises the following components in parts by weight: 20-40 parts of silicone rubber, 40-80 parts of silicone oil and 20-40 parts of neodymium iron boron nanoparticles, and a periodic motion magnet array is designed to drive the low-adhesion magnetic soft composite material antibacterial coating to remove bacterial adhesion. Compared with the prior art, the low-adhesion magnetic soft composite material antibacterial coating provided by the invention is driven by the periodic motion magnet array to remove bacterial adhesion, and has good biocompatibility and magnetic control degerming durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antibacterial coating manufacturing, and specifically relates to a low-adhesion magnetic soft composite antibacterial coating and a preparation method and application thereof. Background Art

[0002] Biofouling refers to the microbial precipitation or biofilm formed on artificial surfaces when proteins, bacteria and other microorganisms penetrate into the water-containing environment. For most medical devices, large ships and industrial equipment, biofouling is undesirable because it can cause great harm to them. For example, bacteria attached to medical devices can lead to serious medical consequences such as surgical infections and implant rejection. Marine microorganisms attached to the surface of large ships will not only corrode the hull, but also increase navigation resistance and cause additional energy consumption. In water cooling systems, biofilm adhesion to pipes will reduce the heat transfer rate and significantly increase the fluid flow resistance and the energy required to pump the fluid.

[0003] In view of the problem of artificial surface antibacterial / removal of bacteria, the design strategy of antibacterial / removal of bacteria coatings is to regulate the surface chemical properties of the coating or design the surface micro-nano structure so that it is difficult for bacteria to survive on the coating surface. Usually, the hydration of the hydrophilic coating and the low surface energy of the super-hydrophobic coating are used to prevent bacteria from adhering to the surface of the material. This type of antibacterial coating design does not cause harm to bacteria. For example, Chinese patent CN117815463A discloses a hydrophilic antibacterial coating and a preparation method thereof. The method contacts a thiol-containing polydopamine coating with a mixed aqueous solution of double-bond functionalized polyethylene glycol and a zwitterionic organic compound having a double bond, and reacts under ultraviolet light to form the hydrophilic antibacterial coating. Chinese patent CN118557809A discloses a high-stability super-hydrophilic super-lubricating antibacterial coating and its preparation method and application. The method synthesizes a quaternized polyethyleneimine polymer with a polyamino antibacterial agent, and forms a firm and stable hydration layer based on the strong hydration induced by the electrostatic action of the zwitterionic component, so as to achieve the super-hydrophilic super-lubricating function and good antibacterial performance of the coating. Chinese patent CN118557809A discloses a super-hydrophilic antibacterial coating sol and its preparation method and application. The method uses the synergistic promotion of a cross-linking agent and a carboxyl-containing compound to simply, conveniently and stably construct a hydrophilic antibacterial polymer on the surface of different substrates. Chinese patent CN115851071A discloses an environmentally friendly super-hydrophobic anti-biofouling self-repairing coating preparation method. The method modifies carbon nanotube silane and nano-copper silane, bonds the modified nano-copper to the modified carbon nanotube, and then loads 2-mercaptobenzimidazole with the nano-copper hybrid, and then mixes with epoxy resin and sprays to obtain a super-hydrophobic anti-biofouling self-repairing coating. Chinese patent CN114231127A discloses a super-hydrophobic antibacterial coating loaded with antibacterial nanocomposite microspheres and a preparation method thereof. The method first soaks silica nano-microspheres in dopamine solution, silver nitrate solution and D-cysteine ​​solution in sequence to prepare multi-layer antibacterial nano-composite microspheres functionalized with nano-silver and D-cysteine, then sprays bisphenol A diglycidyl ether epoxy resin and hydrophobically modified silica nanoparticles on the metal surface to prepare a super-hydrophobic coating substrate, and finally sprays the antibacterial nano-composite microspheres onto the super-hydrophobic substrate to prepare a super-hydrophobic antibacterial coating.

[0004] On the other hand, heavy metals and oxides with bactericidal effects are introduced on the surface of the coating to kill bacteria. For example, Chinese patent CN112451748A discloses a method for preparing a silk fibroin-based bimetallic antibacterial coating, which reduces the concentration of nanosilver and nanogold particles by in-situ reduction of silk fibroin by ultraviolet radiation, and introduces a polydopamine auxiliary layer on the surface of the metal substrate, which greatly enhances the binding performance of the metal and the silk fibroin-based bimetallic antibacterial coating, achieving a long-term and efficient synergistic bactericidal function. Chinese patent CN101073434A discloses a long-acting, fixed, sustained-release silver nanometal antibacterial coating and a preparation method thereof, which synthesizes nanometal silver particles of different sizes and morphologies through process control, and uses chemical bonding technology to fix the nanometal particles on different substrate surfaces to obtain a nano antibacterial coating.

[0005] However, antibacterial coatings based on surface modification and surface microstructure design have not yet overcome the problem of antibacterial durability. Antibacterial coatings based on bactericides such as heavy metals and oxides will pollute the environment and produce serious side effects, limiting their scope of application. Summary of the invention

[0006] The purpose of the present invention is to solve at least one of the above problems and to provide a low-adhesion magnetic soft composite antibacterial coating and its preparation method and application, so as to solve the problems of low durability of antibacterial coatings in the prior art and toxic substances in the formula, thereby achieving good durability and sterilization effect.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a low-adhesion magnetic soft composite antibacterial coating, wherein the magnetic soft composite is cured and then subjected to directional saturation magnetization, and a saturation swelling treatment is performed on the surface to obtain the low-adhesion magnetic soft composite antibacterial coating, wherein the magnetic soft composite comprises, by weight, 20-40 parts of silicone rubber, 40-80 parts of silicone oil, and 20-40 parts of neodymium iron boron nanoparticles. .

[0009] Furthermore, the magnetic soft composite material includes 20 parts of silicone rubber, 40 parts of silicone oil and 40 parts of neodymium iron boron nanoparticles in parts by weight.

[0010] Furthermore, the viscosity of the silicone oil is 100 cst-5000 cst, and the size of the NdFeB nanoparticles is 200 nm-20 μm.

[0011] Furthermore, the viscosity of the silicone oil is preferably 1000 cst.

[0012] Furthermore, the elastic modulus, curing time, curing temperature and magnetically driven deformation amplitude of the composite material can be designed by regulating the silicone oil content, silicone oil viscosity and NdFeB nanoparticle content.

[0013] Furthermore, the composite material is preferably a NdFeB / Ecoflex composite material.

[0014] The second technical solution of the present invention is to provide a method for preparing the low-adhesion magnetic soft composite material antibacterial coating as described above, which is characterized by comprising: coating and curing the magnetic soft composite material, performing directional saturation magnetization through a directional magnetization magnetic field, and spraying a swelling agent on its surface for saturation swelling treatment to prepare the low-adhesion magnetic soft composite material antibacterial coating.

[0015] Furthermore, the directional magnetization magnetic field strength is 1.0T-3.5T, preferably 2T.

[0016] Furthermore, the swelling agent is silicone oil, and the viscosity of the silicone oil is 0.65cst-1000cst, preferably 10cst.

[0017] Furthermore, the coating method includes any one of spin coating, spray coating and printing.

[0018] Furthermore, after coating, the composite material is left to level naturally and then cured.

[0019] Furthermore, the curing is performed by heating under vacuum, preferably at 80° C. for 2 hours.

[0020] Furthermore, the preparation method of the composite material includes: mixing silicone rubber and silicone oil, adding NdFeB nanoparticles, and stirring to obtain the composite material.

[0021] Furthermore, the preparation method of the composite material includes: stirring and vacuum degassing silicone rubber to prepare a uniform silicone rubber precursor solution, adding silicone oil thereto, stirring and vacuum degassing to obtain a silicone oil-silicone rubber precursor solution, adding neodymium iron boron nanoparticles thereto, stirring and vacuum degassing to obtain the composite material.

[0022] Furthermore, the composite material is a magnetic soft composite coating material solution.

[0023] The third technical solution of the present invention is to provide an application of the low-adhesion magnetic soft composite antibacterial coating as described above, characterized in that the low-adhesion magnetic soft composite antibacterial coating is driven by designing a periodically moving magnet array to remove bacterial adhesion.

[0024] Furthermore, the periodically moving magnet array drives the low-adhesion magnetic soft composite antibacterial coating to produce periodic dynamic deformation, causing eddy currents to form on the coating surface to remove bacterial adhesion.

[0025] Furthermore, the magnet array generates a periodic motion driving magnetic field to drive the low-adhesion magnetic soft composite antibacterial coating to produce periodic dynamic deformation, so that eddy currents are formed on the coating surface to remove bacterial adhesion.

[0026] Furthermore, the magnet array is installed on an XY two-dimensional motion platform.

[0027] Furthermore, the magnet array is on an XY two-dimensional motion platform, and the XY two-dimensional motion platform is programmed and controlled according to sterilization requirements, thereby controlling the magnet array to perform periodic motion to generate the required periodic motion driving magnetic field.

[0028] Furthermore, the movement speed range of the driving magnetic field in the X direction is 0-30 mm / s, and the movement speed range of the driving magnetic field in the Y direction is 0-30 mm / s.

[0029] The area of ​​a single magnet unit in the magnet array used is 1mm 2 -125 mm 2 The maximum magnetic field strength of the magnet array surface is 100mT-500mT, and the controllable driving magnetic field regulation of 0-300mT can be achieved by changing the distance between the magnet array and the antibacterial coating of the magnetic soft composite material.

[0030] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. The present invention uses silicone oil to saturate and swell the magnetic soft composite material coating, so that a nano oil film is formed on the surface of the magnetic soft composite material, causing the interface between the coating and the bacterial biofilm to change from a solid-solid interface to a solid-liquid interface, greatly reducing the adhesion strength between the coating and the bacterial biofilm. Under the action of the magnetic field, part of the silicone oil on the surface of the saturated and swollen magnetic soft composite material coating is squeezed out, and the oil film on the surface of the coating can be continuously replenished, thereby greatly improving the antibacterial durability of the magnetic soft composite material coating. The magnetic soft composite material coating is saturated and magnetized in a directional strong magnetic field to give the magnetic soft composite material coating a normal internal magnetization profile. Under the action of the same external driving magnetic field, the saturated magnetized magnetic soft composite material is subjected to greater magnetic force and magnetic moment, thereby achieving a larger magnitude of magnetic drive deformation to produce higher intensity eddy currents, and having a better sterilization effect.

[0033] 2. The present invention proposes a magnetically responsive periodic eddy current sterilization method based on a low-adhesion magnetic soft composite antibacterial coating. By designing a periodically moving magnet array to drive the low-adhesion magnetic soft composite antibacterial coating to produce periodic dynamic deformation, eddy currents are formed on the coating surface in a fluid environment to remove bacterial adhesion. Experimental results show that the enhancement of magnetic field strength, motor movement speed, and magnet unit area can effectively remove bacteria and has a good sterilization effect.

[0034] 3. The present invention uses modular magnet units to form a magnet array and installs it on an XY two-dimensional motion platform to form a programmable and controlled patterned motion driving magnetic field. The magnet unit size, arrangement spacing, magnetic field strength, XY two-dimensional motion platform motion speed and trajectory can be designed according to the sterilization requirements to customize the required patterned driving magnetic field, thereby better achieving the sterilization effect.

[0035] 4. The low-adhesion magnetic soft composite antibacterial coating proposed in the present invention does not require surface modification and surface micro-nanostructure design of the coating, nor does it require the introduction of toxic heavy metals, oxides and other bactericides. It relies on the long-term effective magnetic field response deformation of the coating to induce eddy currents to remove bacteria, and has good biocompatibility and durability of magnetically controlled sterilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the preparation process of low-adhesion magnetic soft composite antibacterial coating.

[0037] Figure 2 Schematic diagram of the concave deformation of the antibacterial coating of the magnetic soft composite material driven by the magnet array.

[0038] Figure 3 Schematic diagram of the results of the concave deformation experiment of the antibacterial coating of the magnetic soft composite material in Example 1 driven by the magnet array.

[0039] Figure 4 This is a schematic diagram of the concave deformation area of ​​the magnetic soft composite antibacterial coating of Example 1 moving along the X direction with the magnet array.

[0040] Figure 5 Schematic diagram of magnet array driven Example 1 where deformation of magnetic soft composite antibacterial coating induces eddy currents to remove bacterial adhesion.

[0041] Figure 6Schematic diagram of quantitative characterization of magnetically driven deformation of magnetic soft composite antibacterial coating, wherein A is a schematic diagram of magnetic soft composite deformation driven by magnetic field in Example 1; B is a laser confocal morphology image of magnetically driven deformation of NdFeB / Ecoflex composite material in Example 1; C is a schematic diagram of magnetically driven deformation depth of NdFeB / Ecoflex composite material and Fe3O4 / Ecoflex composite material under the same driving magnetic field and material content parameters; D is a schematic diagram of the relationship between magnetically driven deformation depth of NdFeB / Ecoflex composite material and driving magnetic field intensity; E is a schematic diagram of the relationship between magnetically driven deformation depth of NdFeB / Ecoflex composite material and NdFeB nanoparticle material content; F is a schematic diagram of the relationship between magnetically driven deformation depth of NdFeB / Ecoflex composite material and the ratio of Ecoflex to silicone oil.

[0042] Figure 7 It is a schematic diagram of the wettability characterization of the magnetic soft composite antibacterial coating of Example 1, wherein A is a contact angle diagram of the magnetic soft composite material before and after swelling with silicone oil; B is a schematic diagram of the droplet sliding test of the magnetic soft composite material before and after swelling with silicone oil; C is a schematic diagram of the contact angle hysteresis comparison of aluminum plate, Ecoflex, and magnetic soft composite material before and after swelling with silicone oil.

[0043] Figure 8 Schematic diagram of the surface adhesion test of the magnetic soft composite antibacterial coating of Example 1, wherein A is a schematic diagram of the adhesion of the magnetic soft composite material to the aluminum plate before and after swelling with silicone oil; B is a schematic diagram of the adhesion of the magnetic soft composite material to Ecoflex before and after swelling with silicone oil; C is a schematic diagram of the adhesion of the magnetic soft composite material to PDMS before and after swelling with silicone oil.

[0044] Fig. 9 It is a schematic diagram of particle image velocimetry (PIV) of deformation-induced eddy currents generated by the magnetically driven magnetic soft composite antibacterial coating of Example 1, wherein A is a schematic diagram of the particle image velocimetry (PIV) experimental device for generating eddy currents in a magnetic soft composite material driven by an arrayed magnetic field with periodic reciprocating motion; B is a schematic diagram of the PIV results of a reciprocating motion cycle under the action of an arrayed magnetic field of 300mT (the motor movement speed is 30mm / s); C is a schematic diagram of the flow velocity in the x and y directions within 10 reciprocating motion cycles (the reciprocating motion frequency is about 0.5Hz); D is a schematic diagram of the local flow velocity changes in two reciprocating motion cycles; E is a schematic diagram of the comparison of flow velocity amplitude changes under different magnetic field intensities; F is a schematic diagram of the comparison of flow velocity amplitude changes under different motor movement speeds.

[0045] Fig.10It is a schematic diagram of the fluorescence area coverage of bacteria on the surface of the magnetic soft composite antibacterial coating of Example 1 under different parameters such as magnetic field strength, motor movement speed, and magnet unit area, wherein A is a schematic diagram of the fluorescence area coverage of bacteria on the surface of the magnetic soft composite antibacterial coating in a static state; BD is a schematic diagram of the fluorescence area coverage of bacteria on the surface of the magnetic soft composite antibacterial coating under different magnetic field strengths; EF is a schematic diagram of the fluorescence area coverage of bacteria on the surface of the magnetic soft composite antibacterial coating under different motor movement speeds; GH is a schematic diagram of the fluorescence area coverage of bacteria on the surface of the magnetic soft composite antibacterial coating under different magnet unit areas.

[0046] Fig.11 It is a schematic diagram of the colony forming unit count (CFU) of the magnetic soft composite antibacterial coating of Example 1 under different parameters such as magnetic field strength, motor movement speed, and magnet unit area, wherein A is a schematic diagram of the colony forming unit count (CFU) of the magnetic soft composite antibacterial coating under different magnetic field strengths; B is a schematic diagram of the colony forming unit count (CFU) of the magnetic soft composite antibacterial coating under different motor movement speeds; C is a schematic diagram of the colony forming unit count (CFU) of the magnetic soft composite antibacterial coating under different magnet unit areas. DETAILED DESCRIPTION

[0047] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0048] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available. The silicone rubber (Ecoflex 30-polybutylene adipate terephthalate) used in the examples was purchased from Smooth-On, USA, silicone oil (viscosity of 0.65 cst-5000 cst) was purchased from Dow Corning, USA, and NdFeB nanoparticles (average particle size of 500 nm) were purchased from Foshan Xinnod Materials Co., Ltd.

[0049] The experimental methods without specific conditions in the following implementations are all selected according to conventional methods and conditions, or according to the product instructions. Unless otherwise specified, the experimental instruments used in the present invention are all conventional experimental instruments in the laboratory.

[0050] Example 1

[0051] This embodiment provides a magnetic soft composite antibacterial coating and its preparation method and application:

[0052] First, the magnetic soft composite antibacterial material is prepared: in parts by weight, the magnetic soft composite material includes 20 parts of silicone rubber, 40 parts of silicone oil, and 40 parts of neodymium iron boron nanoparticles. The preparation method of the magnetic soft composite material includes:

[0053] Add 10 g of Ecoflex 30 Part A and 10 g of Ecoflex 30 Part B into a 50 ml beaker, use a mechanical stirrer to stir at 2000 rpm for 30 seconds, and then perform vacuum degassing to prepare a uniform Ecoflex 30 precursor solution, then add 40 g of silicone oil with a viscosity of 1000 cst to the Ecoflex 30 precursor solution, use a mechanical stirrer to stir at 2000 rpm for 5 minutes, and then perform vacuum degassing to prepare a silicone oil-Ecoflex 30 precursor solution, finally add 40 g of neodymium iron boron nanoparticles to the silicone oil-Ecoflex 30 precursor solution, use a mechanical stirrer to stir at 2000 rpm for 10 minutes, and then perform vacuum degassing to obtain the magnetic soft composite material solution, i.e., NdFeB / Ecoflex composite material solution, which is stored in a 4°C medical refrigerator for standby use.

[0054] Next, the magnetic soft composite material solution was used to prepare a low-adhesion magnetic soft composite material antibacterial coating, such as Figure 1 As shown, the magnetic soft composite material solution is first evenly spin-coated on the substrate surface by spin coating and left at room temperature for 5 minutes. After the magnetic soft composite material solution is naturally leveled, the entire sample is transferred to a vacuum drying oven for vacuum treatment and cured at 80°C for 2 hours under vacuum. After the magnetic soft composite coating material solution is completely cured, the magnetic soft composite material coating is magnetized to saturation using a magnetizing magnetic field of 2T±0.2T, and silicone oil with a viscosity of 10cst is sprayed on its surface for interface saturation swelling to prepare a low-adhesion magnetic soft composite antibacterial coating.

[0055] Next, a periodically moving magnet array is designed to drive the low-adhesion magnetic soft composite antibacterial coating to remove bacterial adhesion. Figure 2 As shown, a magnet array is formed by modular magnet units (the area of ​​the magnet unit is 25mm 2 ) drives the low-adhesion magnetic soft composite antibacterial coating to produce arrayed concave deformation. Figure 3 As shown in the figure, when the magnet array is close to the low-adhesion magnetic soft composite antibacterial coating, an array of concave deformation experimental results will be formed on the coating surface. Figure 4 As shown, when the magnet array moves along the X direction, the coating surface will form an array of concave deformation areas that will move along the X direction. Figure 5As shown, the magnet array is installed on an XY two-dimensional motion platform, and the patterned movement of the magnet array is controlled by programming to form a periodic moving driving magnetic field, which drives the low-adhesion magnetic soft composite antibacterial coating to produce periodic dynamic deformation, resulting in the formation of eddy currents on the coating surface in a fluid environment to remove bacterial adhesion.

[0056] Example 2

[0057] This embodiment provides a magnetic soft composite antibacterial coating and a preparation method and application thereof, except that the content of NdFeB nanoparticles added in the preparation process is 20wt%, the rest is the same as Example 1.

[0058] Example 3

[0059] This embodiment provides an antibacterial coating of a magnetic soft composite material and a preparation method and application thereof, except that the ratio of silicone rubber Ecoflex to silicone oil added during the preparation process is 1:1.5, and the content of neodymium iron boron nanoparticles added is maintained at 40wt%, the rest is the same as Example 1.

[0060] Comparative Example 1

[0061] This comparative example provides a magnetic soft composite antibacterial coating and a preparation method and application thereof, except that the added NdFeB nanoparticles are replaced with an equal amount of ferrosoferric oxide during the preparation process, the rest is the same as Example 1.

[0062] Comparative Example 2

[0063] This comparative example provides a magnetic soft composite antibacterial coating and a preparation method and application thereof, which is the same as Example 1 except that the content of NdFeB nanoparticles added during the preparation process is 60wt%.

[0064] Comparative Example 3

[0065] This comparative example provides a magnetic soft composite antibacterial coating and a preparation method and application thereof, except that the ratio of silicone rubber Ecoflex to silicone oil added in the preparation process is 2:1, and the content of neodymium iron boron nanoparticles added is maintained at 40wt%, the rest is the same as Example 1.

[0066] Test Example 1

[0067] like Figure 6 As shown, this test example quantitatively characterizes the magnetically driven deformation in terms of the silicone oil content, the NdFeB nanoparticle material content, and the driving magnetic field strength added during the preparation of the magnetic soft composite antibacterial coating. Figure 6 As shown in -A, after the NdFeB / Ecoflex (NdFeB magnetic soft composite material) of Example 1 is oriented and saturated, the internal magnetic particles will be endowed with a remanence parallel to the magnetization direction. Figure 6As shown in Figure 2-B, under the action of a 300mT±10mT magnet array, the NdFeB / Ecoflex composite material can produce a conical pit deformation with a diameter of about 1.5mm and a depth of about 1066.9μm.

[0068] (1) Effect of magnetite particle material on magnetically driven deformation depth of magnetic soft composite antibacterial coating: Example 1 and Comparative Example 1 were subjected to directional saturation magnetization and magnetic drive. Figure 6 -C shows that under the same magnetic particle content (40wt%) and driving magnetic field (300mT), the deformation depth of Fe3O4 / Ecoflex (ferromagnetic soft composite material) is 226.5μm, which is only 20% of the deformation depth of NdFeB / Ecoflex composite material. It can be seen that NdFeB / Ecoflex composite material can achieve greater deformation and generate higher intensity eddy current under the same driving magnetic field, which is more conducive to removing bacterial adhesion.

[0069] (2) Effect of driving magnetic field intensity on magnetically driven deformation depth of magnetic soft composite antibacterial coating: Example 1 was magnetically driven under different magnetic field intensities, such as Figure 6 -D shows that when the NdFeB content is 40wt% and the ratio of Ecoflex to silicone oil (Ecoflex: silicone oil) is 1:2, the magnetically driven deformation depth of the NdFeB / Ecoflex composite material increases with increasing magnetic field intensity.

[0070] (3) Effect of NdFeB nanoparticle material content on magnetically driven deformation depth of magnetic soft composite antibacterial coating: Example 1, Example 2 and Comparative Example 2 were magnetically driven under different magnetic field intensities. Figure 6 -E, when the driving magnetic field intensity is 300mT and the ratio of Ecoflex to silicone oil (Ecoflex: silicone oil) is 1:2, the magnetically driven deformation depth of the NdFeB / Ecoflex composite material increases with the increase of the NdFeB nanoparticle material content.

[0071] (4) The elastic modulus of the NdFeB / Ecoflex composite material also increases with the increase of NdFeB content. Under the same driving magnetic field, the higher the NdFeB content, the smaller the deformation of the NdFeB / Ecoflex composite material under magnetic drive. In addition, the higher the NdFeB content, the more difficult it is to solidify the NdFeB / Ecoflex composite material.

[0072] (5) Effect of the ratio of Ecoflex to silicone oil on the magnetically driven deformation depth of the magnetic soft composite antibacterial coating: Example 1, Example 3 and Comparative Example 3 were magnetically driven under different magnetic field intensities. Figure 6-F shows that when the driving magnetic field strength is 300mT and the NdFeB content is 40wt%, the magnetically driven deformation depth of the NdFeB / Ecoflex composite material increases with the ratio of Ecoflex to silicone oil. This is because the larger the ratio of Ecoflex to silicone oil, the softer the NdFeB / Ecoflex composite material, and the larger the deformation under the same driving magnetic field. It should be noted that if the ratio of Ecoflex to silicone oil is too large, the NdFeB / Ecoflex composite material will not be able to fully recover after magnetically driven deformation or the recovery response time will be long, which is not conducive to inducing magnetic field response eddy currents to remove bacterial adhesion.

[0073] Test Example 2

[0074] like Figure 7 As shown, this test example characterizes the wettability of the magnetic soft composite antibacterial coating of Example 1: Figure 7 As shown in -A, the contact angles of the magnetic soft composite material before and after swelling with silicone oil are 97.4° and 76.8° respectively. Figure 7 -B, the experimental results show that the magnetic soft composite antibacterial coating has better liquid repellency after being saturated with silicone oil. Figure 7 -C, the contact angle hysteresis of aluminum plate, Ecoflex, and magnetic soft composite material (MSC) are 35°, 25°, and 20°, respectively, while the contact angle hysteresis of magnetic soft composite material (SMSC) after saturated swelling is only 4°. Therefore, the liquid repellency and smaller contact angle hysteresis indicate that the magnetic soft composite antibacterial coating has good anti-solid adhesion performance.

[0075] Test Example 3

[0076] like Figure 8 As shown, this test example tests the surface adhesion of the magnetic soft composite antibacterial coating of Example 1: To further verify the adhesion performance of the magnetic soft composite antibacterial coating, the adhesion of the magnetic soft composite to the aluminum plate, Ecoflex, and PDMS was tested before and after swelling with silicone oil. Figure 8 -A, the experimental results show that the adhesion between the magnetic soft composite material and the aluminum plate is 6.62N, and the adhesion between the magnetic soft composite material and the aluminum plate after saturated swelling with silicone oil is 0.98N, which is reduced by 6.8 times. Figure 8 -B, the adhesion between the magnetic soft composite material and Ecoflex is 7.35N, and the adhesion between the magnetic soft composite material and Ecoflex after saturated swelling with silicone oil is 1.43N, which is reduced by 5.1 times. Figure 8 -C shows that the adhesion between the magnetic soft composite material and PDMS is 8.51N, and the adhesion between the magnetic soft composite material and PDMS after saturated swelling with silicone oil is 1.65N, which is reduced by 5.2 times.

[0077] Test Example 4

[0078] like Fig. 9 As shown, this test example performs magnetic driving on the magnetic soft composite antibacterial coating of Example 1, and then analyzes the deformation induced eddy current generated by the magnetic soft composite antibacterial coating: Fig. 9 -A, a particle image velocimetry (PIV) experimental device is designed in this test case to analyze the eddy current flow field generated by the deformation of the magnetic soft composite material driven by the periodic moving magnetic field. The motor reciprocating speed is set to 30mm / s, the reciprocating stroke is 60mm, and the magnetic field strength of the arrayed magnet group on the surface of the magnetic soft composite material is 300mT. Fig. 9 -B, the PIV experimental results of a reciprocating motion cycle show that the deformation of the magnetic soft composite material causes the fluid on its surface to produce an obvious eddy current flow field. The flow velocity of the fluid on the surface of the magnetic soft composite material changes as shown in Fig. 9 -C, the flow velocity in the X and Y directions shows periodic changes, such as Fig. 9 -D, the PIV results of the first two motion cycles show that the peak flow velocity in the Y direction is about 605.7μm / s, and the peak flow velocity in the X direction is about 454.5μm / s. The magnetic field strength can be adjusted by changing the distance between the arrayed magnet group and the magnetic soft composite material. Fig. 9 -E presents a comparison of the changes in the amplitude of the fluid velocity on the surface of the composite material under magnetic fields of 100mT, 200mT, and 300mT. The experimental results show that the greater the magnetic field intensity, the greater the deformation depth of the magnetic soft composite material, and the greater the amplitude of the fluid velocity on its surface. Further investigation of the influence of the motor movement speed on the fluid velocity on the surface of the composite material under the magnetic field, Fig. 9 -F presents a comparison of the changes in the flow velocity amplitude of the fluid on the composite material surface at motor movement speeds of 10mm / s, 20mm / s, and 30mm / s. The experimental results show that the greater the motor movement speed, the greater the flow velocity amplitude of the fluid on the surface of the magnetic soft composite material.

[0079] Test Example 5

[0080] like Figure 10-11 As shown, this test example performs magnetic drive on the magnetic soft composite antibacterial coating of Example 1, and then performs antibacterial experimental test:

[0081] To verify the antibacterial properties of the antibacterial coating of the magnetic soft composite material, Escherichia coli (E. coli) was first cultured in 5 ml LB medium at 200 rpm and 37 °C in a shaking incubator for 12 h, and then the spectrophotometer was used to measure the antibacterial activity at a wavelength of 600 nm (OD 600) was measured at a cultured bacterial concentration of 0.3. Subsequently, the suspended culture medium was separated by a centrifuge at a speed of 5000rpm for 15 minutes, and a new culture medium was replaced. The bacteria were cultured at 37°C for 10 hours, and the bacterial concentration was diluted to 0.1. Next, the magnetic soft composite antibacterial coating sample was sprayed with ethanol (70vol%), and the coating was disinfected by ultraviolet light for 2 minutes. The sample was then immersed in the bacterial suspension to examine the influence of parameters such as magnetic field intensity, motor movement speed, and magnet unit area on the deformation-induced eddy current removal of bacterial adhesion by the magnetically driven magnetic soft composite antibacterial coating.

[0082] (1) In order to quantitatively analyze the area coverage of bacteria on the coating surface, the coating samples were prepared into multiple groups and cultured under the same conditions. After the culture, the samples were rinsed three times with phosphate buffered saline (PBS) and then stained with a fluorescent labeling reagent. The stained samples were then placed in a dark environment at room temperature for 20 minutes and rinsed twice with PBS solution. The samples were observed using a multiphoton confocal microscope, and the area coverage of the stained bacteria was then analyzed using ImageJ software. Fig.10 As shown in -A, the area coverage of bacteria on the surface of the coating sample in a static state is 24.66%. Fig.10 -B~10-D, when the motor moves at speed V x =30mm / s and magnet unit area a = 25mm 2 When the magnetic field strength increases, the area coverage of bacteria on the surface of the coating sample decreases, which indicates that the greater the applied magnetic field strength, the better the sterilization performance of the magnetic soft composite antibacterial coating. Fig.10 -E, 10-F, when the magnetic field strength B = 300mT and the magnet unit area a = 25mm 2 When the motor speed increases, the area coverage of bacteria on the surface of the coating sample decreases, which means that the faster the motor speed is, the better the antibacterial performance of the magnetic soft composite material antibacterial coating is. This is because the greater the applied magnetic field strength and the motor speed, the greater the eddy current velocity and vorticity induced on the surface of the magnetic soft composite material antibacterial coating, which is more conducive to removing bacterial adhesion, which is consistent with the PIV experimental results in Example 6. Fig.10 -G, 10-H, when the magnetic field strength B = 300mT and the motor speed V x =30mm / s, the area coverage of bacteria on the surface of the coating sample increases with the increase of the magnet unit area, which means that the larger the magnet unit area, the more difficult it is to remove bacterial adhesion.

[0083] (2) In order to further investigate the antibacterial properties of the magnetic soft composite antibacterial coating, the colony forming unit count (CFU) of the magnetic soft composite antibacterial coating under different magnetic field strength, motor speed, magnet unit area and other parameters were also analyzed, as follows:

[0084] First, the PBS-rinsed coating sample was transferred to a beaker containing 5 ml of sterile PBS and treated with water bath ultrasound for 2 minutes at an ultrasound frequency of 350 Hz to remove all bacteria on the surface of the coating sample. The serially diluted bacterial solution was evenly spread on the surface of LB agar and cultured for 20 hours, and then the grown bacteria were counted. Fig.11 As shown, the CFU on the surface of the coating sample in a static state is 147.92×10 3 / ml. Fig.11 -A, when the motor moves at speed V x =30mm / s and magnet unit area a = 25mm 2 When the magnetic field strength increases, the CFU on the surface of the coating sample decreases, which indicates that the greater the applied magnetic field strength, the better the sterilization performance of the magnetic soft composite antibacterial coating. Fig.11 -B, when the magnetic field strength B = 300mT and the magnet unit area a = 25mm 2 When the motor speed increases, the CFU on the surface of the coating sample decreases, which means that the faster the motor speed increases, the better the antibacterial performance of the magnetic soft composite antibacterial coating. Fig.11 -C, when the magnetic field strength B = 300mT and the motor speed V x =30mm / s, the CFU on the surface of the coating sample increases with the increase of the magnet unit area, which further proves that the larger the magnet unit area, the more unfavorable it is to remove bacterial adhesion.

[0085] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A low-adhesion magnetic soft composite antibacterial coating, characterized in that: After the magnetic soft composite material is solidified, it is subjected to directional saturation magnetization and subjected to saturation swelling treatment on its surface to obtain the low-adhesion magnetic soft composite material antibacterial coating. The magnetic soft composite material, in parts by weight, includes 20-40 parts of silicone rubber, 40-80 parts of silicone oil and 20-40 parts of neodymium iron boron nanoparticles.

2. A method for preparing a low-adhesion magnetic soft composite antibacterial coating as claimed in claim 1, characterized in that: include: The soft magnetic composite material is coated and cured, and then oriented saturation magnetization is performed through an oriented magnetization magnetic field, and a swelling agent is sprayed on the surface to perform saturation swelling treatment to prepare the low-adhesion soft magnetic composite material antibacterial coating.

3. The method for preparing a low-adhesion magnetic soft composite antibacterial coating according to claim 2, characterized in that: The intensity of the directional magnetization magnetic field is 1.0T-3.5T.

4. The method for preparing a low-adhesion magnetic soft composite antibacterial coating according to claim 2, characterized in that: The swelling agent is silicone oil.

5. The method for preparing a low-adhesion magnetic soft composite antibacterial coating according to claim 2, characterized in that: The curing is performed by heating under vacuum.

6. The method for preparing a low-adhesion magnetic soft composite antibacterial coating according to claim 2, characterized in that: The preparation method of the magnetic soft composite material comprises: mixing silicone rubber and silicone oil, adding NdFeB nanoparticles, and stirring to obtain the composite material.

7. An application of the low-adhesion magnetic soft composite antibacterial coating as claimed in claim 1, characterized in that: The low-adhesion magnetic soft composite antibacterial coating is driven by designing a periodically moving magnet array to remove bacterial adhesion.

8. The use of a low-adhesion magnetic soft composite antibacterial coating according to claim 7, characterized in that: The magnet array generates a periodic motion driving magnetic field to drive the low-adhesion magnetic soft composite antibacterial coating to produce periodic dynamic deformation, so that eddy currents are formed on the coating surface to remove bacterial adhesion.

9. The use of a low-adhesion magnetic soft composite antibacterial coating according to claim 7, characterized in that: The magnet array is installed on an XY two-dimensional motion platform.

10. The use of a low-adhesion magnetic soft composite antibacterial coating according to claim 7, characterized in that: The area of ​​a single magnet unit in the magnet array used is 1mm 2 -125 mm 2 The maximum magnetic field strength of the magnet array surface is 100mT-500mT, and the controllable driving magnetic field regulation of 0-300mT can be achieved by changing the distance between the magnet array and the antibacterial coating of the magnetic soft composite material.

Citation Information

Patent Citations

  • Production and use for silver nano-metal antibacterial coating

    CN101073434A

  • Method for preparing silk fibroin base bi-metal antibacterial coating

    CN112451748A

  • Super-hydrophobic antibacterial coating loaded with antibacterial nano composite microspheres and preparation method of super-hydrophobic antibacterial coating

    CN114231127A

  • Preparation method of environment-friendly super-hydrophobic anti-biofouling self-repairing coating

    CN115851071A

  • Hydrophilic antibacterial coating, preparation method thereof and medical product

    CN117815463A